2008
DOI: 10.1002/lpor.200810016
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐large effective‐area, higher‐order mode fibers: a new strategy for high‐power lasers

Abstract: This paper describes the physics and properties of a novel optical fiber that would be attractive for building highpower fiber lasers and amplifiers. Instead of propagating light in the fundamental, Gaussian-shaped mode, we describe a fiber in which the signal is forced to travel in a single, desired higher order mode (HOM). This provides for several advantages over the conventional approach, ranging from significantly higher ability to scale mode areas (and hence laser powers) to managing dispersion for ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(82 citation statements)
references
References 37 publications
0
82
0
Order By: Relevance
“…One such rule, which has had ample experimental confirmation, providing for a degree of confidence, is that Δn eff > 10 -4 yields polarization maintaining (PM) fibers in which the orthogonal polarizations of the LP 01 modes remain stable for lengths scales exceeding 100 m. This rule has been successfully implemented in the context of designing large mode area fibers -a counterintuitive but universal phenomenon, discovered recently [35], reveals that Δn eff between LP 0m and LP 1m mode increases with mode order m, and thus higher order HOMs are actually more stable than lower order modes, yielding a scalable pathway for increasing the mode area of fibers, of utility in highpower applications. In these HOM experiments, it was experimentally confirmed that Δn eff > 10 -4 is a reasonable proxy for mode stability [36].…”
Section: Vortex Fiber Designmentioning
confidence: 62%
“…One such rule, which has had ample experimental confirmation, providing for a degree of confidence, is that Δn eff > 10 -4 yields polarization maintaining (PM) fibers in which the orthogonal polarizations of the LP 01 modes remain stable for lengths scales exceeding 100 m. This rule has been successfully implemented in the context of designing large mode area fibers -a counterintuitive but universal phenomenon, discovered recently [35], reveals that Δn eff between LP 0m and LP 1m mode increases with mode order m, and thus higher order HOMs are actually more stable than lower order modes, yielding a scalable pathway for increasing the mode area of fibers, of utility in highpower applications. In these HOM experiments, it was experimentally confirmed that Δn eff > 10 -4 is a reasonable proxy for mode stability [36].…”
Section: Vortex Fiber Designmentioning
confidence: 62%
“…Such modes have earlier been investigated by e.g. Ramachandran et al [8]. We observe that for very high order Bessel-like modes the azimuthal symmetry is broken and the intensity profile of the mode assumes a bowtie shape, we denote these modes bowtie modes.…”
Section: Introductionmentioning
confidence: 75%
“…9. Modes of lower order propagate unstably in any fiber [8], and they are thus not included in the plot. It is observed that the diffraction free propagation distances are much like that of the ideal Bessel-like modes.…”
Section: Free Space Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the grating crosssection is no longer determined by the dopant concentration, more elaborate fiber grating designs are possible: e. g. grating structures within the cladding or highly localized intracore modifications. Especially the latter enable new grating designs that tap the huge potential of higher-order fiber modes [166,167]. Specially polarized feedback can be obtained, e. g. a fully radially polarized beam [168].…”
Section: Discussionmentioning
confidence: 99%